(untitled) (Bioagro, 2026)
The shortage of pastures and forages in the dry tropics during the summer affects livestock productivity. Maize (Zea mays L.) emerges as a viable option due to its biomass production. The objective of this research was to determine the forage potential of three varieties and four hybrids of maize under dry tropical conditions. The study was conducted using a randomized complete block design. Morphological characteristics, green forage yield, dry matter, and crude protein content of seven cultivars were evaluated at a planting density of 83,333 plants·ha⁻¹. The results indicated that the variety Marginal 28-T exhibited the highest green forage yield (51.99 t·ha⁻¹), the hybrid INIA 624 -KILLU SUK stood out in dry matter production (15.22 t·ha⁻¹), a key material for forage conservation and storage, and INIA 610 - Nutrimaiz excelled with the highest crude protein content (10.5%). It is concluded that the cultivars Marginal 28-T, INIA 624 - KILLU SUK, and INIA 610 - Nutrimaiz represent strategic alternatives due to their potential to alleviate forage shortages in dry tropical regions.